Oxford consensus on primary cam morphology and femoroacetabular impingement syndrome: part 2-research priorities on conditions affecting the young person's hip - Dijkstra, HP; Mc Auliffe, S; Ardern, CL; Kemp, JL; Mosler, AB; Price, A; Blazey, P; Richards, D; Farooq, A; Serner, A; McNally, E; Mascarenhas, V; et al. (BMJ Publishing Group, 2022)
Introduction Primary cam morphology is highly prevalent in many athlete populations, causing debilitating hip osteoarthritis in some. Existing research is mired in confusion partly because stakeholders have not agreed on key primary cam morphology elements or a prioritised research agenda. We aimed to inform a more rigorous, inclusive and evidence-based approach to research on primary cam morphology and its natural history by working towards agreement on a set of research priorities for conditions affecting the young person’s hip. Methods An international expert panel—the Young Athlete’s Hip Research (YAHiR) Collaborative—rated research priority statements through an online two-round Delphi exercise and met online to explore areas of tension and dissent. Panellists ranked the prioritised research statements according to the Essential National Health Research (ENHR) ranking strategy. Reporting of results followed REPRISE (REporting guideline for PRIority SEtting of health). Results A diverse Delphi panel (n=65, Delphi rounds 1 and 2; three ENHR strategy surveys: n=49; n=44; n=42) from 18 countries representing six stakeholder groups, prioritised and ranked 18 of 38 research priority statements. The prioritised statements outlined seven research domains: (1) best practice physiotherapy, (2) rehabilitation progression and return to sport, (3) exercise intervention and load management, (4) primary cam morphology prognosis and aetiology, (5) femoroacetabular impingement syndrome prognosis and aetiology, (6) diagnostic criteria, and (7) screening. The panel recommended areas of tension and dissent for the research community to focus on immediately. Conclusion While informing more rigorous, inclusive and evidence-based research, this consensus is a roadmap for researchers, policy-makers and funders to implement research dedicated to reducing the cost and burden of hip disease related to primary cam morphology.